2011
DOI: 10.1159/000331926
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Area of Rat Molar Expanded by Cigarette Smoke Exposure

Abstract: Objectives: Passive smoking is the involuntary inhalation of cigarette smoke (CS) and has an adverse impact on oral health. We examined the effect of CS exposure on caries risk and experimental dental caries. Methods: Experimental dental caries was induced in rat maxillary molars which were inoculated orally with Streptococcus mutans MT8148 and maintained on a cariogenic diet (diet 2000) and high sucrose water during the experimental period. CS-exposed rats were intermittently housed in an animal chamber with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Nicotine also increases extracellular polysaccharides, which can attract other microorganisms, such as Candida albicans , onto the dental plaque [21]. In fact, in vivo, the caries-affected area on the molars was more expanded in cigarette smoke-exposed rats than in control rats [22]. In humans, tobacco smoking was associated with elevated levels of Streptococcus mutans and Lactobacilli [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine also increases extracellular polysaccharides, which can attract other microorganisms, such as Candida albicans , onto the dental plaque [21]. In fact, in vivo, the caries-affected area on the molars was more expanded in cigarette smoke-exposed rats than in control rats [22]. In humans, tobacco smoking was associated with elevated levels of Streptococcus mutans and Lactobacilli [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have only started to unravel some of the potential effects of tobacco smoking on the biology associated with caries development, including alterations in saliva and dental plaque . A recent experiment has also shown that exposure to cigarette smoke expanded the caries‐affected area in maxillary molars of rats . Further research is needed to assess the above pathways as explanations for the link between smoking and caries.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies that controlled for possible confounders, however, dental caries were significantly and independently associated with smoking [21-25]. A cohort study design may allow the inference of causality [21], and the effects of exposure to tobacco contents on the growth and metabolism of Streptococcus mutans [26] and on the expansion of the dental caries area [27] may suggest biological plausibility. A mechanism which acts via this cariogenic microorganism is conceivable, since the effects of tobacco use on periodontal microorganisms [28,29] has been recently added to the list of potential causal pathways [30].…”
Section: Discussionmentioning
confidence: 99%